Implementation Face Recognition in Attendance Process - Zaenuddin (Proceedings of the Informatics Conference, 2022)
Face recognition technology or known as face recognition currently plays an important role in the presence automation process, aiming to verify a person’s identity, facial recognition technology has undergone large-scale improvements. The Impact of Face Recognition allows users to mark attendance with the face recognition feature, to alternate presence with face, and no need anymore biometric or manual attendance, face recognition helps people to present effectively, Although some research on paper findings outline algorithms to be applied in the attendance process with a screening at the beginning before the absence, For example, students or employees can utilize convenient presence with face detection and recognition before manual attendance or biometric, cause biometrics is less efficient, especially